Stability-Guided Formulation of a Light-Sensitive D-LSD Capsule for Clinical Investigation - Bernard Do; Luc Mallet; Maxime Annereau; Danielle Libong; Audrey Solgadi; Florence Vorspan; Muriel Paul; Philippe-Henri Secretan (Pharmaceutics)
Background/Objectives: D-lysergic acid diethylamide (D-LSD) is under investigation as a potential therapeutic strategy for alcohol use disorder (AUD). However, the extreme light sensitivity of D-LSD presents a significant challenge in developing suitable pharmaceutical forms, particularly for clinical trial settings. This study proposes a liquid-filled capsule formulation designed to provide accurate dosing while protecting D-LSD from photodegradation. Methods: To support formulation development and ensure its suitability as an investigational medicinal product, a multi-tiered analytical strategy was employed. This included liquid chromatography coupled with ion mobility spectrometry and mass spectrometry (LC-IM-MS), along with quantum chemical calculations (density functional theory (DFT) and time dependent-DFT (TD-DFT)), to ensure robust and orthogonal structural characterization of degradation products. Results: Photostress studies demonstrated that while D-LSD in solution rapidly degrades into photoisomers and photooxidative byproducts, the capsule formulation markedly mitigates these transformations under ICH-compliant conditions. Conclusions: These findings highlight the essential role of orthogonal stability profiling in guiding formulation development and demonstrate that this approach may offer a viable, photostable platform for future clinical investigation of D-LSD in the treatment of AUD.